POLA PEMBINAAN DALAM PEMBENTUKAN KARAKTER KEDISIPLINAN DAN KEMANDIRIAN ANAK PANTI ASUHAN MUTMAINNAH DI KECAMATAN SOREANG KOTA PAREPARE - Akbar Susianto; Darmawati Darmawati; Ramli Ramli (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
This study aims to find out how the Mutmainnah Orphanage coaching pattern and how the Formation of the discipline and independence of the Mutmainnah Orphanage Children in Soreang District, Parepare City. This study uses a qualitative descriptive method, using a phenomenological approach that is an approach adjusted to seeing the reality that exists in the field by taking into account the rules and provisions in accordance with coaching. The technique used is observation, interview and documentation analysis techniques. The results of this study prove that the pattern of fostering the Mutmainnah orphanage in Soreang Subdistrict, Parepare city, to foster children, where the coaches do five coaching patterns, namely, 1. the implementation of education by sending foster children, 2. acting as a substitute for parents, 3. religious guidance such as five times prayer, recitation and dhikr after evening prayer in congregation, 4. Skills improvement, and 4. community activities. The results of subsequent research on Character Formation of Children's Discipline and Independence at Mutmainnah orphanage, where discipline character building is, 1. discipline time to get up early, 2. discipline of Worship to pray five times and, 3. discipline to study according to the specified schedule . Then the character of independence of foster children is, 1. building self-confidence in foster children by training to communicate and appear in public and, 2. Teaching responsibility for foster children such as doing schoolwork without having to depend on others and participating in orphanage activities .